Mesenchymal stem cells establish a pro-regenerative immune milieu after decellularized rat uterus tissue transplantation. (August 2022) - Sehic, Edina; Thorén, Emy; Gudmundsdottir, Ingigerdur; Oltean, Mihai; Brännström, Mats; Hellström, Mats
Decellularized tissue is generally considered immune privileged after transplantation and is an attractive scaffold type for tissue regeneration, including applications for infertility treatment. However, the immune response following transplantation of decellularized tissue is insufficiently studied, in particular after they have been recellularized with mesenchymal stem cells (MSCs). Therefore, we replaced a large uterus segment with a bioengineered graft developed from decellularized uterus tissue and analyzed the immune response during the first 4 months in acellular or MSCs-recellularized scaffolds in the rat. Immunohistochemistry-stained infiltrating immune cells and plasma levels for 16 cytokines and chemokines were quantified. Results revealed that MSCs created an advantageous microenvironment by increasing anti-inflammatory interleukin 10 levels, and increasing the population of FOXP3 + TRegs and CD163 + M2 macrophages, and by reducing the CD8 + cytotoxic T cell population. Hence, MSCs should be considered an immunotherapeutic cell source with the ability to dictate regeneration success after decellularized tissue transplantation.